PENGARUH STRATEGI BISNIS DAN INOVASI TERHADAP KEUNGGULAN KOMPETITIF PERUSAHAAN - Firanda, Brilian Setia; Moko, Wahdiyat (Jurnal Kewirausahaan dan Inovasi, 2023)
Micro, Small, and Medium Enterprises (MSMEs) have become one of the most rapidly growing industries in several ASEAN countries. The increase in the number of MSME units has resulted in increased business competition. The potential issue is the risk of MSMEs being pushed out of the competition. Therefore, competitive advantage is essential for MSMEs to remain competitive in the industry. Some researchers believe that competitive advantage is influenced by business strategy and innovation. This study aims to determine the influence of business strategy and innovation on competitive advantage among owners of culinary MSMEs in the snack and pastry sector. The research utilizes a non-probability sampling technique called purposive sampling. The sample size used consists of 150 respondents from culinary MSMEs in the snack and pastry sector in Malang City. The data analysis method employed is multiple linear regression analysis using SPSS 26 software. The research instrument is tested for validity, reliability, and classical assumptions. Hypothesis testing is conducted using the F-test and t-test. Based on the analysis results, it shows that (1) business strategy has a significant influence on competitive advantage, and (2) innovation has a significant influence on competitive advantage.